Single Nucleotide Polymorphisms of Pfdhfr and Pfdhps Genes: Implications for Malaria Prophylactic Strategies in Maiduguri, Northeast Nigeria - Sulayman Tunde Balogun; Umar Kyari Sandabe; Olufunke Adebola Sodipo; Kenneth Okwong Okon; Ayodele Oluwasoji Akanmu (Journal of Tropical Medicine, 2021)
Background. The success of Intermittent Preventive Treatment in Pregnancy (IPTp), Intermittent Preventive Treatment in Infancy (IPTi), and Seasonal Malaria Chemoprevention (SMC) depends on sulfadoxine-pyrimethamine (SP) efficacy. Objective. The study determined Single Nucleotide Polymorphisms (SNPs) of Plasmodium falciparum dihydrofolate reductase (Pfdhfr) and dihydropteroate synthase (Pfdhps) in Maiduguri, Northeast Nigeria. Materials and Methods. Giemsa-stained blood smears, capillary blood, and dried blood spot samples were collected from 63 subjects with uncomplicated malaria in Maiduguri between May and October 2018. Plasmodium species was determined and parasite density (PD) was estimated using the smears. Genomic DNA (gDNA) of P. falciparum was extracted from the dried blood spot samples using QIAamp DNA Mini Kit. The gDNA was subjected to nested PCR followed by restriction fragment length polymorphism (RFLP) to determine SNPs at Pfdhfr codons N51I, C59R, and S108N and Pfdhps codons S436A/F, A437G, and K540E. Results. The subjects’ mean age ± standard deviation was 23.6 ± 8.7 (2.0–67.0) years with a geometric mean PD of 8,948 (2,100–13,400) asexual parasites/µl blood. SNPs prevalence at any of the six Pfdhfr and Pfdhps codons was 85.7% (54/63); the prevalence was higher (p<0.05) in Pfdhfr (82.5%; 52/63) than Pfdhps (58.7%; 37/63). Pfdhfr allele 108N (82.5%; 52/63) was the highest (p<0.05) mutant when compared with alleles 51I (60.3%; 38/63) and 59R (66.7%; 42/63). Triple Pfdhfr mutation was observed in 60.3% (38/63) of the isolates and was higher (p<0.05) among female subjects and SP recipients. Prevalence of Pfdhps allele 436A (28.6%; 18/63) was similar (p>0.05) to allele 437G (34.9%; 22/63), with double mutation recorded in 4.8% (3/63). K540E mutation was not observed. Conclusion. Pfdhfr and Pfdhps mutations observed in Maiduguri are suggestive of SP resistance level, and this could constitute a setback to malaria prophylactic strategies in the region if unchecked. Thus, there is a need to investigate the clinical efficacy of SP.